Management of Fishing Safety for Small Fisheries: An Empirical Analysis - Dewa, Adenanthera L. (LifeSciFi, 2023)
This research highlights the significance of fishing vessel safety in the coastal fishing port in Morodemak, Demak, aiming to identify factors influencing safety and vulnerabilities that may compromise it. Employing a mix of quantitative and qualitative methods, the study collects data through surveys, interviews, observations, and historical incident records. The results reveal critical factors impacting fishing vessel safety, including environmental conditions, vessel maintenance, crew experience and training, safety equipment availability, regulatory compliance, and port infrastructure. Understanding these factors enables the formulation of effective safety enhancement strategies and the promotion of safer fishing practices. The research provides valuable insights for policymakers, port authorities, and fishing communities, contributing to the knowledge on fishing vessel safety. The study's recommendations include reduce accidents, safeguard fishermen's well-being, and foster sustainable fishing practices in the Morodemak Port.